Participação da comunidade educativa na gestão escolar - Luísa Veloso; Craveiro, D.; Rufino, M. (Educação e Pesquisa, 2012)
This text discusses the modes of participation of the education community in school management, examining a dimension that has long been present in the Portuguese political agenda. It centers on the analysis of the organizational dimension of 297 Portuguese schools, based on information made available in the external assessment reports for the academic years of 2006/2007, 2007/2008 and 2008/2009. The corpus analyzed made it possible to fulfill two of the central axes of the participation processes: the mode of integration of the community involved in school life, and the processes and limitations inherent to the participation of two groups of agents – those in charge of education and the pupils. Despite the fact that the various images of school organization present in the external assessment reports are similar, the differentiating aspects are significant. The participation processes are not equally consolidated across the different school organizations and their respective territories, and we witness the growing importance of the presence of the various agents in the tasks of school management. This involvement implies a knowledge that has to be increasingly deeper about the processes of construction of cultural learning that permeate the schools. It is possible to detect the presence of different agents in the schools investigated, which follows a change of conception of educative community encompassing pupils, teachers, those in charge of education, and the surrounding community in which schools are inserted.